Efektivitas Konseling Islami Terhadap Pengetahuan, Self-efficacy, Dan Kecemasan Menstruasi Pada Siswa Putri - Khumairo, Aisyah; Yuliasari, Alfiyana; Halimah, Nur; Zahra, Aminatus; Kumalasari, Sukma; Dina, Alifatul (Program Studi Bimbingan Konseling Islam Fakultas Dakwah Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
Menstruation is an important biological process for adolescent girls, yet many female students still experience anxiety and a lack of understanding regarding menstrual management. This study aims to analyze the effectiveness of Islamic counseling on knowledge, self-efficacy, and menstrual anxiety among female students. The research method used a pretest–posttest quasi-experimental design without a control group. The intervention was conducted through Islamic counseling sessions that integrated values from the Qur’an and hadith, discussions, and reproductive health education. The results showed that Islamic counseling significantly improved knowledge (r = 0.71), but did not produce significant changes in self-efficacy and menstrual anxiety. These findings indicate that Islamic counseling is effective in strengthening cognitive aspects, but affective and behavioral changes require repeated interventions and additional support techniques. This study contributes to the development of Islamic-value-based reproductive health interventions that are relevant and implementable in Islamic school settings.